GEOLOGI, ALTERASI DAN MINERALISASI ENDAPAN EPITERMAL SULFIDASI TINGGI TAMBANG RISKA BARAT, LANUT, SULAWESI UTARA - Riana Nugraha, Nuresa
The research area is administratively located in Lanut District, Modayag Subdistrict, Bolaang Mongondow Timur Regency, North Sulawesi Province, and geographically located at 662000 – 662400 mE and 74800 – 75250 mN with an area sized 400x450 meters. Riska is an open-pit mine of high-sulfidation epithermal gold deposit within the Contract of Work area of PT. J Resources. Riska pit had stopped producing since Desember of 2015. The purpose of this research is to determine geological condition, design an alteration-mineralization zone and determine the correlation between Au-Cu-Ag grade and alteration-mineralization zone. To achieve those goals, some methods such as geological and alteration mapping, detailed bore cores logging from 11 different wells, petrographic analysis of 24 samples, mineragraphic analysis of 9 samples, clay mineral analysis using ASD of 40 samples, and assay Au, Cu, Ag geochemistry analysis were used. Lithostratigraphic units of Western Riska pit that formed on Miocene consist of 3 units, they are Lapilli Tuff Unit, Pyroclastic Breccia-Breccia Tuff Unit and Andesitic Lava Unit respectively. All of those units had undergone alteration-mineralization processes on Pliocene. There are four alteration zones in this research location, they are Alunite-Dickite-Quartz Zone, Quartz-Kaolinite Zone, Smectite-Calcite-Illite±Quartz Zone, and Calcite-Chlorite-Felspar sekunder±Quartz Zone. In this research location, pyrite exist in all alteration zones, arsenian pyrite/arsenopyrite-enargite-chalcopyrite exist in Alunite-Dickite-Quartz Zone, and bornite-covellite-goethite-hematite exist as supergene minerals. Mineralization paragenesis can be subdivided into two phases: high sulfidation epithermal and supergene oxidation. Supergen mineralization only observed in fractured zone in Quartz-Dickite-Alunite zone at ?680 msl. High-sulfidation epithermal deposit of Western Riska pit is controlled by geological structure such as ENE – WSW right lateral normal fault that was formed by Inobonto’s regional sinistral faults. High concentration of Au-Cu-Ag ( > cut off grade of Au=0,1 ppm; Cu=1500 ppm; Ag=10 ppm) is associated with Alunite-Dickite-Quartz zone, hydrothermal breccia zone, and supergene zone.